2015
DOI: 10.1371/journal.pone.0133761
|View full text |Cite
|
Sign up to set email alerts
|

Association of Rotating Night Shift Work with BMI and Abdominal Obesity among Nurses and Midwives

Abstract: BackgroundMounting epidemiological evidence suggests that night shift work may contribute to the etiology of increased body weight. The present study aimed to examine association between rotating night shift work and body mass index (BMI), and abdominal adiposity respectively among nurses and midwives.MethodsA cross-sectional study was conducted among 724 female nurses and midwives, aged 40-60 years (354 rotating night shift and 370 daytime workers) in Łódź, Poland, between 2008 and 2011. Information about occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
134
5
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 49 publications
12
134
5
12
Order By: Relevance
“…62 Shift work itself is associated with numerous poor health outcomes similar to those seen with sleep loss and circadian misalignment, such as diabetes, obesity, hypertension, impaired reproductive health, cognitive function, and cancer. 40,61,[63][64][65][66] It is likely that duration of shift work exposure, the number of night shifts worked per month, and the age at which a person started shift work also play a role in the development of poor health outcomes. For example, shift work is associated with poor cognitive function that is related to the duration of shift work exposure particularly when exposure was more than 10 years.…”
Section: Shift Work Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…62 Shift work itself is associated with numerous poor health outcomes similar to those seen with sleep loss and circadian misalignment, such as diabetes, obesity, hypertension, impaired reproductive health, cognitive function, and cancer. 40,61,[63][64][65][66] It is likely that duration of shift work exposure, the number of night shifts worked per month, and the age at which a person started shift work also play a role in the development of poor health outcomes. For example, shift work is associated with poor cognitive function that is related to the duration of shift work exposure particularly when exposure was more than 10 years.…”
Section: Shift Work Disordermentioning
confidence: 99%
“…67 Nurses who work more than 8 night shifts per month are 3.9 times more likely to be obese. 65 Using the Nurses' Health Study II, Ramin and colleagues 68 found that ever working shift work was associated with obesity, greater caloric intake, and short sleep duration. These associations were impacted by age at which shift work was performed and if shift work was performed before age 25 this was associated with fewer risk factors than shift work later in life.…”
Section: Shift Work Disordermentioning
confidence: 99%
“…Moreover, night workers were more likely than day workers to become obese (14,15) and to have unhealthy lifestyle (16) such as smoking (17), unhealthy diet (16) or low physical activity (18), which may contribute to the risk of cancer and affect hormonal milieu and sex hormone metabolism (19,20).…”
mentioning
confidence: 99%
“…Cross-sectional and prospective studies identify shift work as an independent predictor of excess body weight, 35-37 and indicate that abdominal obesity, the obesity phenotype carrying the greatest risk, is prominent. 36 These harmful effects of shift work are conceivably a function of circadian disruption. Due to nocturnal lighting exposure, levels of urinary 6-sulfatoxymelatonin, the main melatonin metabolite, are lower in rotating night shift workers 38 than daytime workers.…”
Section: Consequences Of Circadian Disruptionmentioning
confidence: 99%